2015
DOI: 10.1371/journal.pone.0137680
|View full text |Cite
|
Sign up to set email alerts
|

Levels of sP-selectin and hs-CRP Decrease with Dietary Intervention with Selenium and Coenzyme Q10 Combined: A Secondary Analysis of a Randomized Clinical Trial

Abstract: Background/ObjectivesInflammation and oxidative stress are central in many disease states. The major anti-oxidative enzymes contain selenium. The selenium intake in Europe is low, and supplementation with selenium and coenzyme Q10, important anti-oxidants, was evaluated in a previous study. The aim of this study was to evaluate response on the inflammatory biomarkers C-reactive protein, and sP-selectin, and their possible impact on cardiovascular mortality.Subjects/Methods437 elderly individuals were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 48 publications
4
39
0
1
Order By: Relevance
“…This might indicate that the part most diseased died to a greater extent in the placebo group compared to the active treatment group also during the time after the termination of the intervention. An explanation might be a decrease of the progression of the cardiovascular disease during the intervention as could be seen from increased inflammatory activity that is reduced by the intervention [ 37 ] and where at the end result, if not given intervention, increased atherosclerosis and macroscopic cardiovascular injuries as a result could be registered up to 6 years after the termination of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This might indicate that the part most diseased died to a greater extent in the placebo group compared to the active treatment group also during the time after the termination of the intervention. An explanation might be a decrease of the progression of the cardiovascular disease during the intervention as could be seen from increased inflammatory activity that is reduced by the intervention [ 37 ] and where at the end result, if not given intervention, increased atherosclerosis and macroscopic cardiovascular injuries as a result could be registered up to 6 years after the termination of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A dysregulation of the expressed selenoproteins makes an active supplementation of Se an even more promising adjuvant intervention . In this context, a prospective randomized, double‐blind, placebo‐controlled study evaluated the effects of combined chronic supplementation of Se (200 μg organic Se) and 200 mg coenzyme Q10 per day on the severity of chronic heart failure, all‐cause mortality, and cardiovascular mortality . The intervention was performed for 4 years, and the authors observed that chronic treatment with Se and Q10 resulted in a reduced inflammatory status in these patients and significantly reduced cardiovascular mortality assessed after 10 years …”
Section: The Role Of Se In Cardiac Surgerymentioning
confidence: 99%
“…The administration of low doses of Se at only a few time points will probably have no significant effects on the circulating Se blood levels, bioavailability, or the patient's clinical outcome . In contrast, a more frequent administration of Se might have more pronounced effects on reducing new infections in critically ill patients . Additionally, there is no consensus about whether Se should be administered as a bolus or as a continuous infusion.…”
Section: The Role Of Se In Cardiac Surgerymentioning
confidence: 99%
“…Results from a Swedish study published in 2015 indicated improved vitality and overall score of health related quality-of-life as a result of intervention with Se and coenzyme Q 10 to an elderly population with mean baseline plasma Se of 67 μg/L (Johansson et al 2015 ). The same intervention study also demonstrated a decreased inflammatory activity as registered by the biomarkers sP-selectin and hs-CRP (Alehagen et al 2015 ). The Se supplement dose in this latter study was 200 μg/day, given as selenized yeast.…”
Section: The Metal-based Hypothesis Of Neuroinflammationmentioning
confidence: 87%